NHT Cooperative Model For Learning Independence Of Pancasila Education In Elementary School: Why Teacher-Centered Must Change? - Lindha Puspitaning Cahya; Nur Mala Ni’matul Fadhilah; Nur Setyo Jatiningtyas; Deni Zein Tarsidi (Academic Solution Publisher, 2024)
Civic education in elementary schools aims to instill Pancasila values as the basis for learner behavior. However, Civic education is often teacher-centered which makes learners tend to be passive. Therefore, a more active approach, such as the NHT model, is needed to create an interactive and collaborative learning atmosphere. This research uses a literature review by collecting data from relevant scientific articles and journals in the last ten years. It was analyzed by combining theory and best practice to understand the application of NHT in the context of Civic education. The results show that the NHT model encourages learners to work in small groups collaboratively. Through this approach, learners actively discuss, solve problems and take responsibility for their role in the group. This model also creates a fun learning environment and supports the development of social skills. In conclusion, the application of the NHT model is effective in creating learner-centered learning, thus increasing their active involvement in the learning process.